Empowering State High School 3 Mandau Duri Teachers: Training on E-Book Creation with Flipbook Application - Afrizona Niken Trisna; Jismulatif Jismulatif; Syofia Delfi; Dita Dita; Dahnilsyah Dahnilsyah; Suhardi Suhardi (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Abstract This community service project aims to train secondary school teachers at SMA Negeri 3 Mandau, Duri-Riau, to create electronic books (e-books) using Flipbook software. The objective is to equip teachers with the necessary skills to develop e-books as online and face-to-face instruction materials. These e-books allow students to access them anytime, anywhere, particularly during remote learning. The training program spanned two weeks and included training and mentoring sessions, with 30 participants in attendance. Flipbuilder and Kvisoft Flipbook Maker were utilized as flipbook maker applications. The training yielded positive results, demonstrating participants' proficiency in creating and designing e-books for online use. The future goal is to enhance these e-books further and publish them as teaching materials with an ISSN. Keywords: e-book, flipbook maker, English material, Senior high School